Implementation of Formative Evaluation on Arabic Debate Learning to Improve Arabic Language Skills - Primasti Nur Yusrin Hidayanti; Faris Maturedy (Al-Fusha : Arabic Language Education Journal, 2023)
A formative evaluation process on Arabic debate learning needs to be carried out. This is a form of anticipation of student weaknesses in speaking skills ahead of the final exam. The use of Arabic debate methods is used to train students in improving Arabic language skills, especially in the field of mahārah al-kalām. This study aims to evaluate debate learning using formative evaluation. The evaluation is carried out during the learning process. Researchers use descriptive qualitative research methods with field research models. The results of this study show that the formative evaluation process is carried out by providing feedback and input from each student. In addition, students are also asked to provide evaluations through research sheets. The achievement index scale used as a reference for educators in evaluating the assessment score that will be obtained by students is 100 with a value scale of 75-87. This evaluation can help Arabic teachers to reflect on the learning that has been done.